Intracellular recognition of pathogens and autophagy as an innate immune host defence - Yano, Tamaki (Oxford University Press, 2011)
Pathogen recognition is the first and crucial step in innate immunity. Molecular families involved in the recognition of pathogens and activation of the innate immune responses in immunoreactive cells include the Toll-like receptor family in mammals and the peptidoglycan recognition protein (PGRP) family in Drosophila, which sense microorganisms in an extracellular or luminal compartment. Other emerging families are the intracellular recognition molecules for bacteria, such as nucleotide binding and oligomerization domain-like receptors in mammals and PGRP–LE in Drosophila, several of which have been shown to detect structures of bacterial peptidoglycan in the host cell cytosol. Exciting advances in recent studies on autophagy indicate that macroautophagy (referred to here as autophagy) is selectively induced by intracellular recognition molecules and has a crucial role in the elimination of intracellular pathogens, including bacteria, viruses and parasites. This review discusses recent studies related to intracellular recognition molecules and innate immune responses to intracellular pathogens, and highlights the role of autophagy in innate immunity.